A scientometric analysis of BIM studies in facilities management. Issue 2 (5th December 2018) - Hilal, Mustafa; Maqsood, Tayyab; Abdekhodaee, Amir
Abstract : Purpose: The purpose of this paper is to statistically classify and categorize Building Information Modelling (BIM)-Facility Management (FM) publications in order to extract useful information related to the adoption and use of BIM in FM. Design/methodology/approach: This study employs a quantitative approach using science mapping techniques to examine BIM-FM publications using Web of Science (WOS) database for the period between 2000 and April 2018. Findings: The findings guide the researchers who are interested in the BIM-FM model by providing visual maps analysis of that area in a simple, easy and readable way. In addition, they help the researchers to understand which authors and journals to consider when dealing with BIM-FM topics. Finally, knowledge gaps in this domain can be identified easily using the findings of the Scientometric analysis. Research limitations/implications: First, the results of the analysis depend on the database that has been extracted from WOS, and therefore it carries any of WOS's limitations in terms of how much it covers the published studies. Another limitation is that the study is based on exploration of "what" questions, rather than "how" and "why". These limitations represent the hot topics to be addressed in future research. Originality/value: This research is the first to conduct the Scientometric Analysis of BIM-FM topics, in which 68 top-ranked publications were systematically examined using a Science Mapping method through VOSviewer software.